Some observations on the pathogenesis of syringomyelia. Issue 11 (November 1981) - Newman, P K; Terenty, T R; Foster, J B
Abstract : The pathogenesis of most cases of syringomyelia remains obscure although a modification of the hydrodynamic theory of Gardner allows a logical surgical approach to treatment. Data are presented confirming a high incidence of traumatic birth in patients with syringomyelia who have a Chiari malformation or basal arachnoiditis, but demonstrating no increase in traumatic birth in patients with the Chiari malformation but no syringomyelia. A traumatic birth may be the factor responsible for creating the potential for syringomyelia in those individuals with the embryological defect of the Chiari anomaly.